2018
DOI: 10.1126/sciadv.aat3198
|View full text |Cite
|
Sign up to set email alerts
|

Practical water production from desert air

Abstract: Next-generation MOF device and material for water production from desert air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
401
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(466 citation statements)
references
References 24 publications
16
401
0
3
Order By: Relevance
“…In this regard, Al‐MOFs are of special interest as they combine high operating temperatures, convenient syntheses in aqueous media, and high natural abundance of the metal sources. Moreover, their exceptional chemical stability in both aqueous and organic media makes this class of materials ideal for applications that are unsuitable for most MOFs, such as moisture harvesting, adsorption‐driven heat exchange, and water remediation . Unfortunately, the synthesis of highly crystalline Al‐MOFs is a long‐standing challenge as most of these can only be obtained as nanocrystalline powders and such limitations are known to have detrimental effects on MOFs’ porosity and sorption capacity .…”
Section: Introductionsupporting
confidence: 69%
“…In this regard, Al‐MOFs are of special interest as they combine high operating temperatures, convenient syntheses in aqueous media, and high natural abundance of the metal sources. Moreover, their exceptional chemical stability in both aqueous and organic media makes this class of materials ideal for applications that are unsuitable for most MOFs, such as moisture harvesting, adsorption‐driven heat exchange, and water remediation . Unfortunately, the synthesis of highly crystalline Al‐MOFs is a long‐standing challenge as most of these can only be obtained as nanocrystalline powders and such limitations are known to have detrimental effects on MOFs’ porosity and sorption capacity .…”
Section: Introductionsupporting
confidence: 69%
“…As shown in Figure 3a, PGF delivers the rapid moisture sorption with an equilibrium water uptake of 5.20 g g −1 at an RH of 100%, much higher than that of pure rGO and PAAS foam with the value of 0.26 and 1.29 g g −1 , respectively. Compared with previous reports (Table S1, Supporting Information), [13][14][15][16][24][25][26][27][28][29][30][31][32][33][34] PGF in this study shows an outstanding ability for moisture capture in the full range of humidity, which will largely broaden the applications in diverse environments. The microporous structure of PGF provides effective transport channels and an enlarged contact area for moisture, and oxygen functional groups of PAAS can spontaneously capture water molecules through hydrogen bonding ( Figures S3 and S4, Supporting Information).…”
Section: Doi: 101002/adma201905875mentioning
confidence: 51%
“…

contaminated inevitably by the impurities, such as microorganisms, fine particulate matters (PM), and toxic gases like sulfur oxides (SO x ). [13][14][15][16] However, MOF-801 only worked in a narrow RH range (<20% RH) with low water uptake, and the quality of the oozed water from PNI-PAAm/Alg hydrogel was uncertain for the risk of impurities. For instance, metalorganic frameworks (MOFs) like MOF-801 could harvest 0.25 g g −1 water at a relative humidity (RH) of 20%, and poly(Nisopropyl acrylamide)/sodium alginate (PNIPAAm/Alg) polymer hydrogel demonstrated 0.6 g g −1 water uptake at the RH of 80%, respectively.

…”
mentioning
confidence: 99%
“…In 2017, Yaghi and Wang and co-workers first demonstrated a porous MOF (MOF-801, [Zr 6 O 4 (OH) 4 (fumarate) 6 ]) exhibited superior ability to capture water from the atmosphere at low humidity levels (as low as 20%) by using low-grade heat from natural sunlight. [204] The results found that this device can produce 100 g of water per kilogram of MOF-801 per day-and-night cycle after carefully modifying the condenser and the title angle to the sunlight. Surprisingly, 2.8 L water per kilogram of MOF daily can be delivered at low humidity levels without any energy input.…”
Section: Photothermal-assisted Water Harvesting From Airmentioning
confidence: 95%